2008
DOI: 10.1182/blood.v112.11.2803.2803
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Leukocytosis, Thrombocytosis and JAK2V617F Mutation with Thrombotic Events in Myeloproliferative Disorders (MPD’s)

Abstract: Background: Essential thrombocythemia (ET) and Polycythemia vera (PV) are clonal diseases, present at diverse ends in the spectrum of MPD’s. Recently, there has been an increased interest in the association of leukocytosis, thrombocytosis and the presence of JAK2V617F mutation with the risk of thrombosis in patients with ET. Although, leukocytosis and the presence of JAK2V617F mutation has been proposed as prognostic indicators for thrombosis, the correlation of thrombocytosis with thrombotic risk remains uncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is suggested that this mutation likely causes thrombosis through multiple mechanisms, including activation of platelets and granulocytes [39,40]. More recently, the association of leucocytosis and JAK2 mutation with thrombotic events has been confirmed in a retrospective study of 108 patients with ET [41]. Increased rate of vascular complications in ET have been associated with two variables, age and previous thrombotic history [42].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that this mutation likely causes thrombosis through multiple mechanisms, including activation of platelets and granulocytes [39,40]. More recently, the association of leucocytosis and JAK2 mutation with thrombotic events has been confirmed in a retrospective study of 108 patients with ET [41]. Increased rate of vascular complications in ET have been associated with two variables, age and previous thrombotic history [42].…”
Section: Discussionmentioning
confidence: 99%